Electronic clinical reminder and quality of primary diabetes care. Issue 2 (April 2019) - Wu, Shannon S.; Chan, Kitty S.; Bae, Jaeyong; Ford, Eric W.
Highlights: Clinical reminder use and practice size are associated with performing services to manage diabetes. Clinical reminder use and practice size are not associated with counseling services. Resources are needed to reduce gaps in diabetes care between solo and non-solo practices. Abstract: Aims: To study the association of EMR's clinical reminder use on a comprehensive set of diabetes quality metrics in U.S. office-based physicians and within solo- versus multi-physician practices. We conducted a retrospective cohort study on visits made by adults with diabetes identified from the National Ambulatory Medical Care Survey (2012–2014). Methods: Multiple logistic regression is used to test for associations between clinical reminder use and recommended services by the American Diabetes Association. Results: Of 5508 visits, nationally representing 112, 978, 791 visits, 31% received HbA1c tests, 13% received urinalysis test, and <10% received retinal or foot exams. Main effects of practice size and clinical reminder use were found for HbA1c, urinalysis, and foot exams. We find no statistically significant relationship to suggest that clinical reminder use improve diabetes process guidelines for solo practices. Conclusions: Resource efforts, beyond clinical reminders, are needed to reduce gaps in primary diabetes care between solo and non-solo practices.